Effects of landscape features on population genetic variation of a tropical stream fish, Stone lapping minnow, Garra cambodgiensis, in the upper Nan River drainage basin, northern Thailand - Jaisuk,Chaowalee; Senanan,Wansuk (PeerJ, 2018)
Spatial genetic variation of river-dwelling freshwater fishes is typically affected by the historical and contemporary river landscape as well as life-history traits. Tropical river and stream landscapes have endured extended geological change, shaping the existing pattern of genetic diversity, but were not directly affected by glaciation. Thus, spatial genetic variation of tropical fish populations should look very different from the pattern observed in temperate fish populations. These data are becoming important for designing appropriate management and conservation plans, as these aquatic systems are undergoing intense development and exploitation. This study evaluated the effects of landscape features on population genetic diversity of Garra cambodgiensis, a stream cyprinid, in eight tributary streams in the upper Nan River drainage basin (n = 30–100 individuals/location), Nan Province, Thailand. These populations are under intense fishing pressure from local communities. Based on 11 microsatellite loci, we detected moderate genetic diversity within eight population samples (average number of alleles per locus = 10.99 ± 3.00; allelic richness = 10.12 ± 2.44). Allelic richness within samples and stream order of the sampling location were negatively correlated (P < 0.05). We did not detect recent bottleneck events in these populations, but we did detect genetic divergence among populations (Global FST = 0.022, P < 0.01). The Bayesian clustering algorithms (TESS and STRUCTURE) suggested that four to five genetic clusters roughly coincide with sub-basins: (1) headwater streams/main stem of the Nan River, (2) a middle tributary, (3) a southeastern tributary and (4) a southwestern tributary. We observed positive correlation between geographic distance and linearized FST (P < 0.05), and the genetic differentiation pattern can be moderately explained by the contemporary stream network (STREAMTREE analysis, R2 = 0.75). The MEMGENE analysis suggested genetic division between northern (genetic clusters 1 and 2) and southern (clusters 3 and 4) sub-basins. We observed a high degree of genetic admixture in each location, highlighting the importance of natural flooding patterns and possible genetic impacts of supplementary stocking. Insights obtained from this research advance our knowledge of the complexity of a tropical stream system, and guide current conservation and restoration efforts for this species in Thailand.
Keywords: Microsatellite variation; Spatial genetic variation; Landscape genetics; Tropical stream fish; Garra cambodgiensis; Upper Nan River